2023
DOI: 10.2147/jbm.s392146
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Helicobacter pylori Infection and Anemia Among Adult Dyspeptic Patients Attending Kiryandongo General Hospital, Uganda

Abstract: Purpose To determine the prevalence of anemia and its association with Helicobacter pylori infection among adult dyspeptic patients. Patients and Methods A cross-sectional study was conducted among 283 dyspeptic patients at Kiryandongo General Hospital, in Uganda. A structured questionnaire was administered to capture demographic and clinical characteristics of study participants. Four milliliters of blood were then collected into an EDTA vacu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
0
0
Order By: Relevance
“…Our result was not in conformity with that of Haile et al, who observed anemia proportion in H. pylori-positive individuals to be 29.19% [32]. We found the prevalence of anemia incomparable with findings of various other investigations: in Uganda by Asiimwe et al (19.9%) [62]; Cuba (24.6%) by Pita-Rodríguez et al [63]; Butajira (26.9%) by Kibru et al [59]; Karachi (25%) by Abdul et al [64]; and Brazil (20%) [65]. This variation in the prevalence of anemia could be expounded by differences in sample size, methods adopted, and characteristics of the populations considered for studies.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…Our result was not in conformity with that of Haile et al, who observed anemia proportion in H. pylori-positive individuals to be 29.19% [32]. We found the prevalence of anemia incomparable with findings of various other investigations: in Uganda by Asiimwe et al (19.9%) [62]; Cuba (24.6%) by Pita-Rodríguez et al [63]; Butajira (26.9%) by Kibru et al [59]; Karachi (25%) by Abdul et al [64]; and Brazil (20%) [65]. This variation in the prevalence of anemia could be expounded by differences in sample size, methods adopted, and characteristics of the populations considered for studies.…”
Section: Discussioncontrasting
confidence: 97%
“…We observed the prevalence of different kinds of anemia computed based on marginal distribution was 67.7 % IDA (Figure 5a), 35% anemia (Figure 5b), 43% microcytic anemia, and 57% normocytic anemia (Figure 5c). Kibru et al reported all the morphotypes of anemia in the H. pylori-infected group: microcytic, normocytic, macrocytic, and macrocytic anemia [59]; however, we observed only normocytic and microcytic anemia morphotypes, which suggests the H. pylori infection may cause IDA by decreasing iron absorption and minimizing Hb concentration owing to iron deficiency [62].…”
Section: Discussioncontrasting
confidence: 83%
“…Where: N= sample size Z= is the standard normal variable estimated at 1.96 (adopted from the Z distribution table) at a 95 % confidence level P= P is the estimated proportion; considering the prevalence of H. pylori in Kiryandongo General Hospital, at 42.4% =0.424 (Asiimwe et al, 2023). q = 1-p, (1-0.424) = 0.576 d = 0.05, Represents the error allowed n= 1.96 x 1.96 x 0.424 x 0.576 0.05 x 0.05 =375 respondents 375 respondents will be considered for the study.…”
Section: Sample Size Determinationmentioning
confidence: 99%